2021
DOI: 10.3390/ma14247561
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Deep Cryogenic Treatment on Wear and Galling Properties of High-Speed Steels

Abstract: New approaches to improving wear resistance with an affordable and noncomplex technology, such as deep cryogenic treatment, (DCT0), are receiving attention. The aim of this study is to investigate the effect of DCT on the friction and wear performance of high-speed steels. AISI M2, AISI M3:2 and AISI M35 were heat-treated under different conditions, and then investigated under dry sliding conditions. Tribological testing involved different contact conditions, prevailing wear mechanisms and loading conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 25 publications
(39 reference statements)
0
24
0
Order By: Relevance
“…Moreover, CT at −196 °C for 25 or 40 h (sequence A) had no effect on the abrasive wear resistance of S390 Microclean steel, but CT at −196 °C for 40 h after austenitising at 1130 °C (lower than the manufacturer's recommended temperature) led to the maximum anti-galling performance of the given steel, as more undissolved carbides had been maintained in its microstructure [166,167]. Similarly, the anti-galling performance was also improved for AISI M3:2 steel [318]. For AISI M2, M3:2, and M35 high-speed steels, there was a moderate improvement in anti-galling performance after CT at −196 °C for 24 h (following sequence A) [121,318].…”
Section: High-speed Steelsmentioning
confidence: 96%
“…Moreover, CT at −196 °C for 25 or 40 h (sequence A) had no effect on the abrasive wear resistance of S390 Microclean steel, but CT at −196 °C for 40 h after austenitising at 1130 °C (lower than the manufacturer's recommended temperature) led to the maximum anti-galling performance of the given steel, as more undissolved carbides had been maintained in its microstructure [166,167]. Similarly, the anti-galling performance was also improved for AISI M3:2 steel [318]. For AISI M2, M3:2, and M35 high-speed steels, there was a moderate improvement in anti-galling performance after CT at −196 °C for 24 h (following sequence A) [121,318].…”
Section: High-speed Steelsmentioning
confidence: 96%
“…Research on the wear process on machine components has been carried out for many years [ 10 , 11 ]. Researchers primarily seek to reduce the effects of wear, which can be caused by friction [ 12 ], corrosion [ 13 , 14 ], or the impact of additional abrasive particles [ 15 ]. In practice, it is rare that there is only one determinant of wear.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Leskovšek and Podgornik [24] found that the adhesive and galling resistance of cryotreated (at À196 °C for either 25 or 40 h) P/M high-speed steel against AISI 304 austenitic stainless steel (150 HV 10) S390 increased by %30%. More recently, other researchers evaluated the galling resistance of cryogenically treated AISI M2, M3:2, and M35 steel against aluminum (Al) material and reported reductions in adhered Al material of 30%, 20%, and 50%, respectively, after cryogenic treatment at À196 °C for 24 h. [25] In contrast to high-speed steels, the information on antigalling properties of cryogenically treated cold work tool steels such as D-class materials or Cr-V steels is lacking to date. As the Uddeholm Vanadis 6 is recommended, besides others, also for long-run tooling of materials where mixed (adhesive or abrasive-adhesive) wear is the dominating failure mechanism, [26] the main motivation of the current study is to study and understand the behavior of Vanadis 6/soft counterpart sliding couple under the circumstances of dry sliding.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Leskovšek and Podgornik [ 24 ] found that the adhesive and galling resistance of cryotreated (at −196 °C for either 25 or 40 h) P/M high‐speed steel against AISI 304 austenitic stainless steel (150 HV 10) S390 increased by ≈30%. More recently, other researchers evaluated the galling resistance of cryogenically treated AISI M2, M3:2, and M35 steel against aluminum (Al) material and reported reductions in adhered Al material of 30%, 20%, and 50%, respectively, after cryogenic treatment at −196 °C for 24 h. [ 25 ]…”
Section: Introductionmentioning
confidence: 99%